PENERAPAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PERPAJAKAN BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 2009 TENTANG KETENTUAN UMUM DAN TATA CARA PERPAJAKAN DAN UNDANG-UNDANG NOMOR 7 TAHUN 2021 TENTANG HARMONISASI PERATURAN PERPAJAKAN - H. Syaroji Karta; Emmy Yunita (Justici, 2022)
ABSTRACT Tax payments are a manifestation of state obligations and the participation of Taxpayers (WP) to directly and jointly carry out tax obligations for state financing and national development. In accordance with the philosophy of tax law, paying taxes is not only an obligation, but is the right of every citizen to participate in the form of participation in state financing and national development. The type of research that the author uses is normative legal research, which is a legal research method carried out by examining library materials or secondary data.